Diseño y adaptación de chasis, carrocería y sistema eléctrico a un vehículo tipo buggy - Tello Guzmán, Javier Rosalino (2012)
Diseño y adaptación de chasis, carrocería y sistema eléctrico a un vehículo tipo buggy.